An Interpretation of the So-Called Paraffin Dirt of the Gold Coast Oil Fields - Albert Brokaw (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1918)
THE so-called ?paraffin dirt" of the Gulf Coast oil fields has been con¬sidered an indication of the possible presence of oil and gas, and not a few wells have been brought in solely on the basis of such evidence. In a sense, it may be empirically justified as evidence of the presence of oil or gas, though it cannot be said to be infallible. If the writer is correctly informed, its association with oil and gas was pointed out by Lee Hager some years ago, and while it is commonly mentioned by geologists and operators in conversation, no discussion seems to have found its way into print. The present interpretation is based on laboratory study rather than on field investigation, and is put forth with the hope of stimulating discussion which shall lead to more complete understanding. The term "paraffin dirt" has been applied to soils with a peculiar texture, which has been described' as "curdy" or "rubbery." When moist, the material breaks much after the fashion of "green" cheese. It is rubbery under compression, but does not resemble rubber in tenacity or cohesion. When dry, the material ranges from hard clods to a horny mass of high tensile strength. The shrinkage in drying is very great, especially in the hornlike matter. The moist material ranges in color from dark brown in the specimens rich in organic matter to grayish in specimens containing more inorganic matter. All of the specimens studied were readily attacked by molds, which in some cases grew in great profusion on the samples. Samples exhibited a rather characteristic "swampy" or "mucky" odor when wet, and a characteristic odor of humic soils when moist.